Enhancement of availability of high calcareous phosphorite by neutralization of acid effluent and composting of cattle manure - Shamuratov Sanjarbek; Baltaev Umid; Achilova Sanobar; Alimov Umarbek; Namazov Shafoat; Usanbaev Najimuddin (E3S Web of Conferences, 2023)
In this article, the influence of acidic effluent (AE) neutralization process, the production of raw fatty acids of cotton soap stock, on the change in the applicability of phosphate powder (PP) and mineralized mass (MM), which are low-grade phosphorites of the Central Kyzylkum, has been studied. It was found that with wide changes in the mass ratios of AE : PP and AE: MM (from 100:10 to 100:40) at a temperature of 60 °C and a time duration of 30 min, the content of the relative assimilable forms of phosphorus in 2% citric acid are approximately from 1.95 to 1.63 and from 3.67 to 1.72 folds more with a content of 17.52 and 9.11% of the assimilable form of P2O5 for citric acid PP and MM respectively. Activated phosphorite obtained at a mass ratio of AE: PP and AE: MM = 100:20 was introduced into cattle manure at various mass ratios from 100:8 to 100:20 for composting for 3 months. The prepared mixture was moistened periodically with water to a moisture content of 65-70%. It has been established that with an increase in the content of activated phosphorite and the duration of composting time, it leads to an increase in the content of humic acids, fulphonic acids, and water-soluble organics in the compost products. On the other hand, the duration of composting tends to increase the degree humification above 60%. The approach of acid treatment and composting of carbonate phosphorites can be included as a promising technology for obtaining effective organomineral fertilizers for creating an organic garden in agriculture.